2007
DOI: 10.1016/j.expneurol.2006.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Increase of cannabinoid CB1 receptor density in the hippocampus of streptozotocin-induced diabetic rats

Abstract: In the hippocampus, impaired neurophysiology, compromised neurogenesis, and eventually apoptosis accompany cognitive deficits in insulinopenic (type-1) diabetes (T1D). The underlying pathological mechanisms remain to be defined. The hippocampus has a high density of the cannabinoid type 1 receptor (CB 1 R), which has been shown to control several brain functions affected by diabetes, such as synaptic plasticity, glucose utilisation, memory consolidation and cognition, and maturation and survival of hippocampal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 33 publications
3
16
0
1
Order By: Relevance
“…Endocannabinoids may control energy metabolism via CB 1 R. Recent evidence demonstrates that CB 1 R antagonists have beneficial effects in obese patients with type 2 diabetes (55). In addition, the hippocampal densities of CB 1 R protein and specific CB 1 R binding sites are significantly increased in the animal model of streptozotocin-induced type 1 diabetes (13). Our recent report also demonstrated that palmitic acid induces CB 1 R activation in proximal tubule cells, suggesting that hyperlipidemia increases CB 1 R activation, which may be associated with the onset of diabetic nephropathy (28).…”
Section: Discussionmentioning
confidence: 80%
“…Endocannabinoids may control energy metabolism via CB 1 R. Recent evidence demonstrates that CB 1 R antagonists have beneficial effects in obese patients with type 2 diabetes (55). In addition, the hippocampal densities of CB 1 R protein and specific CB 1 R binding sites are significantly increased in the animal model of streptozotocin-induced type 1 diabetes (13). Our recent report also demonstrated that palmitic acid induces CB 1 R activation in proximal tubule cells, suggesting that hyperlipidemia increases CB 1 R activation, which may be associated with the onset of diabetic nephropathy (28).…”
Section: Discussionmentioning
confidence: 80%
“…In the present study, CB 1 receptor protein appears to be down-regulated in nerve cells grown in conditions mimicking hyperglycemia and in neurons from diabetic rats. A study recently published by Duarte et al (2007) revealed decreased CB 1 mRNA expression in the hippocampus of diabetic rats, concomitant with an increase in CB 1 protein density. Although the mRNA data are in agreement with our findings, differences in neuronal CB 1 protein expression between hippocampus (increased in Duarte et al, 2007) and DRG (decreased in the present study) from STZinduced diabetic rats may reflect site-specific signaling pathways involved in mRNA translation, e.g., activation of the key rate-limiting translational pathway mammalian target of rapamycin in hippocampal neurons (Duarte et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidences show that hippocampus and frontal cortex are involved in spatial learning and memory [39][40][41]. In our previous experiments, we employed Cresyl Violet staining to detect the survival of neurons in hippocampal and frontal cortex regions to study the effect of astaxanthin treatment on neurons in DE mice.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In addition, treatment with astaxanthin could significantly improve impaired performance of learning and memory in the DE+AST group compared to the DE group. Our findings demonstrated that astaxanthin could prevent cognitive impairments induced by hyperglycemia in DE mice.Furthermore, astaxanthin treatment has no effect on normal mice, which was shown by the N+AST group.Mounting evidences show that hippocampus and frontal cortex are involved in spatial learning and memory [39][40][41]. In our previous experiments, we employed Cresyl Violet staining to detect the survival of neurons in hippocampal and frontal cortex regions to study the effect of astaxanthin treatment on neurons in DE mice.…”
mentioning
confidence: 99%